2022
DOI: 10.3390/m1345
|View full text |Cite
|
Sign up to set email alerts
|

O6-[(2″,3″-O-Isopropylidene-5″-O-tbutyldimethylsilyl)pentyl]-5′-O-tbutyldiphenylsilyl-2′,3′-O-isopropylideneinosine

Abstract: Cyclic adenosine diphosphate ribose (cADPR) is a cyclic nucleotide involved in the Ca2+ homeostasis. In its structure, the northern ribose, bonded to adenosine through an N1 glycosidic bond, is connected to the southern ribose through a pyrophosphate bridge. Due to the chemical instability at the N1 glycosidic bond, new bioactive cADPR derivatives have been synthesized. One of the most interesting analogues is the cyclic inosine diphosphate ribose (cIDPR), in which the hypoxanthine replaced adenosine. The effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…They reported that five compounds of newly synthesized have IC 50 values less than 5.95 µM. In our continuous attempts to develop novel potent bioactive agents ( Abdel-Jalil et al, 2015 , El-ajaily et al, 2019 , El-Barasi et al, 2020 , Eleya et al, 2011 , Hussain et al, 2008 , Ibad et al, 2011 , Kamel et al, 2022a , Kamel et al, 2022b , Mahal, 2015a , Mahal et al, 2010 , Mahal et al, 2011 , Mahal et al, 2015b , Mahal et al, 2015c , Mahal et al, 2019 , Mahal et al, 2021 , Marzano et al, 2022 , Mohapatra et al, 2021 , Salman et al, 2011 , Salman et al, 2020 , Salman et al, 2022 , Yang et al, 2017 , Yang et al, 2018 , Zinad et al, 2020a , Zinad et al, 2020b , Zinad et al, 2020c , Zinad et al, 2020d , Zinad et al, 2021a , Zinad et al, 2021b , Zinad et al, 2022 , Zinad et al, 2023a , Zinad et al, 2023b ), we aim at this study to investigate the molecular docking and DFT calculation of potent anticancer agents of tetrahydrocurcumin.…”
Section: Introductionmentioning
confidence: 98%
“…They reported that five compounds of newly synthesized have IC 50 values less than 5.95 µM. In our continuous attempts to develop novel potent bioactive agents ( Abdel-Jalil et al, 2015 , El-ajaily et al, 2019 , El-Barasi et al, 2020 , Eleya et al, 2011 , Hussain et al, 2008 , Ibad et al, 2011 , Kamel et al, 2022a , Kamel et al, 2022b , Mahal, 2015a , Mahal et al, 2010 , Mahal et al, 2011 , Mahal et al, 2015b , Mahal et al, 2015c , Mahal et al, 2019 , Mahal et al, 2021 , Marzano et al, 2022 , Mohapatra et al, 2021 , Salman et al, 2011 , Salman et al, 2020 , Salman et al, 2022 , Yang et al, 2017 , Yang et al, 2018 , Zinad et al, 2020a , Zinad et al, 2020b , Zinad et al, 2020c , Zinad et al, 2020d , Zinad et al, 2021a , Zinad et al, 2021b , Zinad et al, 2022 , Zinad et al, 2023a , Zinad et al, 2023b ), we aim at this study to investigate the molecular docking and DFT calculation of potent anticancer agents of tetrahydrocurcumin.…”
Section: Introductionmentioning
confidence: 98%